Adipokines as Potential Biomarkers in Rheumatoid Arthritis - Annalisa Del Prete; Valentina Salvi; Silvano Sozzani (Mediators of Inflammation, 2014)
Rheumatoid arthritis (RA) is a chronic systemic inflammatory autoimmune disease characterized by severe joint injury. Recently, research has been focusing on the possible identification of predictor markers of disease onset and/or progression, of joint damage, and of therapeutic response. Recent findings have uncovered the role of white adipose tissue as a pleiotropic organ not only specialized in endocrine functions but also able to control multiple physiopathological processes, including inflammation. Adipokines are a family of soluble mediators secreted by white adipose tissue endowed with a wide spectrum of actions. This review will focus on the recent advances on the role of the adipokine network in the pathogenesis of RA. A particular attention will be devoted to the action of these proteins on RA effector cells, and on the possibility to use circulating levels of adipokines as potential biomarkers of disease activity and therapeutic response.